Structural Properties of Concrete Materials Containing RoadCem. (16th June 2015) - Holmes, Niall
Abstract : This paper presents findings from a preliminary study to assess the structural and material properties of a nonstandard, concrete type mix containing RoadCem, a traditional soil stabilising additive. Two different mixes determined the effect of adding RoadCem in terms of compressive and flexural strengths, breaking strain, thermal expansion and contraction behaviour, permeability using a falling head, and Young's modulus. RoadCem is a fine powder containing alkali metals and synthetic zeolites which are complemented with a complex activator. RoadCem modifies the dynamics and chemistry of cement hydration by enhancing the crystallisation process and forming longer needle crystalline structures. It reduces the heat of hydration with an early strength development. Varying the volume in the mix varies the viscosity and alters curing times while maintaining the water cement ratio. The results from this study have shown a modest increase in compressive strength and Young's modulus with improvements in thermal performance, particularly at low temperatures. The flexural strength of the two mixes was similar with a much reduced permeability in the RoadCem mix. The results demonstrate the improved performance of concrete incorporating RoadCem but further improvements are possible by using a better graded aggregate and controlling the maximum dry density and moisture contents.